The Effect of Training on Postural Control in Dyslexic Children - Goulème, Nathalie (PLoS One, 2015)
The aim of this study was to explore whether a short postural training period could affect postural stability in dyslexic children. Postural performances were evaluated using Multitest Equilibre from Framiral. Posture was recorded in three different viewing conditions (eyes open fixating a target, eyes closed and eyes open with perturbed vision) and in two different postural conditions (on stable and unstable support). Two groups of dyslexic children participated in the study, i.e. G1: 16 dyslexic participants (mean age 9.9 ± 0.3 years) who performed short postural training and G2: 16 dyslexic participants of similar ages (mean age 9.1 ± 0.3 years) who did not perform any short postural training. Findings showed that short postural training improved postural stability on unstable support surfaces with perturbed vision: indeed the surface, the mean velocity of CoP and the spectral power indices in both directions decreased significantly, and the cancelling time in the antero-posterior direction improved significantly. Such improvement could be due to brain plasticity, which allows better performance in sensory process and cerebellar integration.